Penggunaan Maksim Kualitas Pada Wacana Opini Surat Kabar Harian Kompas Edisi Februari 2017 Dan Implikasinya Sebagai Bahan Ajar Dalam Pelajaran Bahasa Indonesia SMA/SMK Kelas XII - Choiriyah, Marotul; , Dra. Atiqa Sabardila, M. Hum (2017)
This study aims to identify the maxim of quality in the text of daily opinion Kompas newspaper edition of February 2017. This type of research using qualitative research. Data collection in research using techniques refer and note. In the data analysis using orthographic method. The orthographic technique is used to analyze data on Kompas daily newspaper. The orthographic pad technique involves a determinant of writing in the form of a maxim of quality in the opinion discourse. The data will be sorted using the basic technique of Determining Elements (PUP) technique. Based on the analysis of the text of opinion, it is found that the maxim of quality is used by writers of Kompas daily newspaper opinion to reinforce the ideas conveyed related to the issues. Maximize the quality of facts shown by the author to convince readers of the issue. The newspaper's opinion writer expresses his opinion with a view to influencing the reader to approve and support the idea so that it has the same perception. In addition, the maxim of quality can be used as teaching materials in the Indonesian class XII SMA / SMK KD. 4.2 produces the text of opinion. Through the facts of the truth, learners can use it as a theme in preparing the text of opinion.